Perancangan Sistem Informasi Pengelolaan Parkir Di Fakultas Keguruan Dan Ilmu Pengetahuan Universitas Sebelas Maret Surakarta - Yudi Adi Cahyanto; Chairullah Naury; Mursid Dwi Hastomo (Indonesian Journal of Information Technology and Computing (IMAGING), 2024)
The problems that are often encountered in conventional parking systems include the unavailability of complete, informative and interactive parking information. The manual parking system usually uses two ticket papers for each vehicle, where one ticket paper is held by the vehicle owner and the other ticket paper is installed in the vehicle. If the ticket paper in the owner's vehicle is lost or someone who is not responsible deliberately exchanges the ticket paper, chaos will occur and of course this is the responsibility of the parking attendant. This manual parking system is considered less effective because it consumes energy and time. Based on the description of the background mentioned above, it can be formulated that the problem to be solved in this study is "How to design a Parking Management Information System at the Teaching and Education Faculty (FKIP) Sebelas Maret University Surakarta (UNS)". Boundary The problem that the author discusses in this study focuses more on parking management at FKIP UNS. This designed system can manage parking fees and also print parking tickets. The method used for system development uses the Software Development Life Cycle (SDLC) with the Waterfall model. The programming language used is PHP Native and MySQL database.